ANALYSIS OF STUDENTS’ UNDERSTANDING OF IDIOMATIC EXPRESSIONS AND ITS USE IN THEIR ESSAY: A CASE STUDY - Dalilah Fathma; Nurlela Nurlela; Muhammad Yusuf (JOALL (Journal of Applied Linguistics and Literature), 2020)
This research aims to find out the types of idiomatic expressions which are used by the students in their English essay and to describe on how far is their understanding of idiomatic expressions. In conducting this research, the writer applies qualitative approach by using content analysis to observe the types of idioms found in the students’ essays and doing an interview sessions in order to assess their understanding of idiomatic expressions.Based on the analysis, it is found that there are two types of idiomatic expressions found in the students’ essays. Both types are consisted of each one idiom for one student, those are A cup of tea categorized as Compound and Drop your jaw categorized as Verb + object/complement (and/or adverbial). Whilst, the results of their understanding of idiomatic expressions through interview session show that 6 of 7 were not able in passing the first facet of Six Facets of Understanding which is Explanation and categorized as the students do not understand about idiom, while 1 of 7 students could pass all facets and categorized as the only student who understands about idioms. The results show that actually the 4th semester of English Department students of Universitas Sumatera Utaraare not that familiar with idioms since five of seven of them did not use idiom in their essays and six of seven of them could not pass the facets of understanding.